The five people you meet in heaven - Albom, Mitch, 1958- (Albom, Mitch, 1958- Heaven books, 2003)
Weaves three stories about 83-year-old Eddie, the head maintenance person at Ruby Point Amusement park. Eddie meets 5 individuals in heaven each with a story to share, a secret to reveal and a lesson. They have profound meanings for Eddie on the real purpose of his life.